Pertanggungjawaban Pejabat Pembuat Akta Tanah atas Akta Jual Beli yang Dibatalkan - Harly Irianto Christo Sembung (JURNAL ILMIAH NUSANTARA, 2024)
This research aims to examine and analyze the responsibilities of the Land Deed Official (PPAT) and the legal protection for third parties concerning canceled Sale and Purchase Deeds. The research questions include: what is the responsibility of the PPAT in creating a canceled Sale and Purchase Deed, and what is the legal protection for third parties regarding canceled land rights certificates. This is a normative legal study that reviews the relevant legislation on the issues investigated, using both statutory and case-based approaches analyzed descriptively and qualitatively.The findings of this thesis are as follows: the responsibility of the Notary/PPAT in creating a canceled Sale and Purchase Deed means that the PPAT is responsible for all deeds they create if they contain legal defects. The responsibilities imposed on the PPAT can be administrative, civil, and criminal. If a PPAT is proven to have committed violations related to their duties, they may face sanctions such as written warnings, temporary suspension, honorable dismissal, or dishonorable dismissal. The imposition of these sanctions depends on the quantity and quality of the violations committed by the PPAT. Legal protection for third parties regarding canceled land rights certificates includes preventive protection, where the PPAT must create deeds in accordance with applicable laws and regulations, and repressive protection, which involves filing a lawsuit against the land certificate already issued by the National Land Agency (BPN) in court. Parties who feel harmed by deeds made by the PPAT can report to the Head of the Land Office or the Association of Land Deed Officials (IPPAT).